The nature and significance of the political ideal of the Rule of Law: Hayek, Buchanan, and beyond - Kliemt, Hartmut; Justus Liebig University Giessen (My University, 2024)
Hayek and Buchanan endorsed Böhm's “private law society” as expressive of the ideal of a government of laws, and not of men. But they also acknowledged that among the many, the enforceability of legal custom, adjudication, and legislation must be politically guaranteed by a state. Due to unavoidable state-involvement, risks of excessive rent-seeking and authoritarian arbitrary government loom large once “rules of rule change” enable sophisticated forms of ruling by law. Even if in WEIRDS (Western, Educated, Industrialized, Rich, Democratic, Societies) legal rules are enacted, modified, and derogated exclusively according to legal “rules of rule change,” the prevalence of the key attributes of “generality, certainty, and equality of enforcement” of the Rule of Law is in no way guaranteed. — The paper addresses this and the role, nature, and significance of constraining ruling by law through practicing the “political ideal of the Rule of Law”.
Keywords: ddc:330